Hospital concentration and bed capacity. Issue 6 (30th March 2022) - Garmon, Christopher
ABSTRACT: The COVID-19 pandemic has highlighted the importance of hospital bed capacity. Some policy experts claim that hospital mergers and lax antitrust oversight contributed to hospital bed shortages in the United States. This paper investigates the relationship between hospital concentration and bed capacity using public data and panel data methods. No evidence is found that increasing hospital concentration leads to reduced capacity. If anything, the evidence suggests the opposite: a small positive association between concentration and hospital bed capacity. The evidence suggests that the antitrust agencies are correct to focus on price, cost, quality, and access to care instead of overall bed capacity in their evaluation of hospital mergers.